2019
DOI: 10.1027/1015-5759/a000396
|View full text |Cite
|
Sign up to set email alerts
|

The Nomological Network of Emotion Recognition Ability

Abstract: Abstract. The ability to recognize other people’s emotions from their face, voice, and body (emotion recognition ability, ERA) is crucial to successful functioning in private and professional life. The Geneva Emotion Recognition Test (GERT; Schlegel, Grandjean, & Scherer, 2014 ) is a new instrument to measure ERA in a more ecologically valid way than previous tests. In this article, we report the results of five studies examining the test’s construct validity with a total N of 1,284. We found that the GERT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…This might be explained by communalities from a general socio-emotional abilities factor: the general ability to navigate social situations, or a commonsense factor of social interaction, which also helps with successful faking. Evidence for such a socio-emotional abilities factor exists (Geiger et al Forthcoming a;Hildebrandt et al 2015;MacCann et al 2014;Schlegel et al 2019;Schlegel and Scherer 2018), but its relation with faking ability is still poorly understood because prior work either only used a single test for emotion recognition (Geiger et al 2018), or only used a self-report emotional intelligence questionnaire (Pelt et al 2018) which represents socio-emotional abilities poorly (Olderbak and Wilhelm 2020).…”
Section: Correlates Of Faking Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This might be explained by communalities from a general socio-emotional abilities factor: the general ability to navigate social situations, or a commonsense factor of social interaction, which also helps with successful faking. Evidence for such a socio-emotional abilities factor exists (Geiger et al Forthcoming a;Hildebrandt et al 2015;MacCann et al 2014;Schlegel et al 2019;Schlegel and Scherer 2018), but its relation with faking ability is still poorly understood because prior work either only used a single test for emotion recognition (Geiger et al 2018), or only used a self-report emotional intelligence questionnaire (Pelt et al 2018) which represents socio-emotional abilities poorly (Olderbak and Wilhelm 2020).…”
Section: Correlates Of Faking Abilitymentioning
confidence: 99%
“…This research suffers from challenges in assessment that resulted in a proliferation of constructs, leading to jingle and jangle fallacies (Olderbak and Wilhelm 2020). However, studies on some of these constructs, namely socio-emotional abilities (with the term socio-emotional abilities, we refer to abilities related to processing, producing, and regulating social and emotional information), have demonstrated their importance in expanding models of intelligence (Hildebrandt et al 2011(Hildebrandt et al , 2015MacCann et al 2014;Olderbak et al 2019a;Schlegel et al 2019Schlegel et al , 2020Schlegel and Scherer 2018) and predicting real-life outcomes (Côté et al 2010;Joseph and Newman 2010;MacCann et al 2020). Still, most research in this field has focused on basic socio-emotional abilities, such as emotion perception and recognition.…”
Section: Introductionmentioning
confidence: 99%
“…In several models of EI, the accurate interpretation of non-verbal emotional information is considered to be a precondition for successfully understanding and managing others’ emotions, thus facilitating interpersonal communication and individual goal attainment (Schlegel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research and several meta-analyses have demonstrated that higher ERA is associated with a wide range of psychosocial benefits, such as better mental health, social adjustment, relationship quality, and workplace performance (e.g., [4,5]). At the same time, deficits in ERA have been related to various mental disorders, such as schizophrenia [6], and to maladaptive traits such as trait anger, anxiety, and alexithymia [7]. The accurate recognition of emotions in others allow one to better understand and anticipate other people’s behavior, to adapt one’s own actions accordingly, and to smooth interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ERA test used in this study, the GERT [3], measured ERA by presenting participants with short video clips with sound in which actors express 14 different emotions, and was developed and validated using Item Response Theory [3,7]. Given that in everyday life emotions are most often expressed dynamically and simultaneously in the face, voice, and body, the GERT responds to calls from several researchers for a broader, more comprehensive, and more ecologically valid assessment of ERA (e.g., [2,28]).…”
Section: Introductionmentioning
confidence: 99%